2004
DOI: 10.1038/sj.eye.6701323
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmic features of Turner's syndrome

Abstract: Turner's syndrome is one of the most common of all chromosomal abnormalities and is associated with significant ophthalmic morbidity. Turner's 1938 account included two patients with strabismus, and hitherto the condition has generated more interest among orthoptists than ophthalmologists. This systematic review of the literature seeks to redress the balance. Based on the pooled data of 274 patients with Turner's syndrome, it is the most complete evaluation so far of the prevalence and severity of ophthalmic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 25 publications
(24 reference statements)
3
41
0
2
Order By: Relevance
“…Refractive errors are present in about 40% of girls and women with TS, with increased prevalence of both hyperopia and myopia (391). Importantly, strabismus and amblyopia each occur in roughly one-third of females with TS.…”
Section: Ophthalmologymentioning
confidence: 99%
“…Refractive errors are present in about 40% of girls and women with TS, with increased prevalence of both hyperopia and myopia (391). Importantly, strabismus and amblyopia each occur in roughly one-third of females with TS.…”
Section: Ophthalmologymentioning
confidence: 99%
“…3,4 Retinal diseases, however, are not frequently mentioned, 1,2 and peripheral RN is rare. Sickle cell retinopathy was a concern in our case, but it is very rare in the Chinese 5 ; the results of blood examination were normal in the current case.…”
Section: Discussionmentioning
confidence: 94%
“…A collection of 6 publications is the most numerous study of female patients with Turner syndrome [7] which was found by us in literature, and it is a collection of ocular defects of 274 female patients with Turner syndrome. However, none of the works fi led here nor the total conclusions were interested in the relationship between eye symptomatology and karyotype, additionally, and, furthermore, the observations should be considered with care as studies with different numbers of female patients (from 7 do 177), from different authors and at various time periods (1974-1990) were compared.…”
Section: Discussionmentioning
confidence: 99%
“…Colour vision deficiency is described mainly in the forms of impairments in the area of the red-green spectrum in the literature in Turner syndrome [7,14,24] which reflects the reality that red and green retinal photo pigment is localized on the long arm of the X chromosome. The change of colour vision is described in 8% in men and 0,5% in women in the general population [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation